Weather-resistant waterborne polyurethane ink and preparation method thereof

By preparing weather-resistant water-based polyurethane inks, the coordinated combination effect of modified acrylate emulsion and high dispersion nano SiO2, graphene oxide and hexagonal boron nitride is solved, and the high weather resistance and good performance of the ink layer after aging is achieved.

CN119799065AActive Publication Date: 2025-04-11HANGZHOU LINAN SHENGHENG DECORATION MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510014039.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Water-based polyurethane inks have poor weather resistance and are susceptible to UV rays, moisture and temperature changes, resulting in material fading, discoloration, cracking, powdering and decreasing strength, limiting the diversified direction of its applications.

Method used

By preparing a weather-resistant water-based polyurethane ink, it uses a modified acrylate emulsion and its internal high-dispersion nano SiO2, graphene oxide and hexagonal boron nitride to fully exert the co-mixing effect to improve the weather resistance of the ink. Specific steps include: using PEG-2000 and isophorone diisocyanate to prepare an aqueous polyurethane emulsion, nano SiO2 ball milling treatment to improve dispersion, and mixing it with modified acrylate emulsion, graphene oxide and hexagonal boron nitride to improve weather resistance.

Benefits of technology

Through this technical method, the weather resistance of water-based polyurethane ink is significantly improved. The light loss rate of the ink layer after artificial aging is no more than 30%, the color difference value is no more than 1.2, the powder is slight, and the peeling area is no more than 0.1%, which has high use value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of printing ink, and particularly discloses weather-resistant waterborne polyurethane printing ink and a preparation method thereof. The invention relates to a preparation method of weather-resistant waterborne polyurethane ink. The preparation method comprises the following steps: I, preparing a waterborne polyurethane emulsion; iI, mixing the high-dispersity nano SiO2, styrene, an acrylic acid compound and chlorinated polyether resin, and reacting under the condition of adding an initiator, a surfactant and a silane coupling agent to obtain a modified acrylate emulsion; and III, dispersing the waterborne polyurethane emulsion, the modified acrylate emulsion, graphene oxide, hexagonal boron nitride, a pigment and an auxiliary agent in a solvent, and uniformly mixing to obtain the weather-resistant waterborne polyurethane ink. According to an ink layer formed after coating and curing of the weather-resistant waterborne polyurethane ink, the gloss loss rate after aging is not higher than 30%, the chromatic aberration value is not larger than 1.2, pulverization is very slight or even no pulverization exists, the stripping area is not larger than 0.1%, and the weather-resistant waterborne polyurethane ink has good weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inks, and in particular to a weather-resistant water-based polyurethane ink and a preparation method thereof. Background Art

[0002] Water-based polyurethane ink is an environmentally friendly ink that uses water as a dispersion medium. The water-based polyurethane binder is evenly dispersed in the water in the form of particles. This ink does not contain volatile organic solvents, so it is non-flammable, non-toxic, odorless, energy-saving and environmentally friendly. It has received more and more attention in recent years, and its applications in screen printing, composite film printing, etc. are becoming increasingly widespread. It can also be used for 3D printing. By introducing nanofibers and solvent-induced rapid curing technology, 3D printing at room temperature can be achieved, and the printed structure has excellent mechanical properties and resilience. At the same time, fluorescent ink can be prepared by introducing fluorescent monomers. It has good acid and alkali resistance, heat resistance and bonding strength to the substrate, and is suitable for fluorescent anti-counterfeiting applications on plastic packaging films.

[0003] However, the defects of water-based polyurethane ink cannot be ignored. Due to the presence of hydrophilic groups in its molecular structure, these groups are easily affected by ultraviolet rays, moisture and temperature changes in the natural environment, resulting in aging phenomena such as fading, discoloration, cracking, powdering and strength loss in the material. In other words, its weather resistance is poor. This problem greatly limits the application of water-based polyurethane ink in a more diversified direction. In order to improve the weather resistance of water-based polyurethane ink, researchers have adopted a variety of modification methods, including introducing silicone groups or organic fluorine groups into water-based polyurethane to improve its water resistance, and adding cross-linking agents to enhance the intermolecular forces of water-based polyurethane to form a more stable network structure. These measures can effectively improve the weather resistance of water-based polyurethane ink. However, with actual use, people have found that the hardness and wear resistance of silicone-modified water-based polyurethane are poor, and it is easy to be damaged during use; the environmental friendliness of organic fluorine-modified water-based polyurethane is not good. If the ink layer is damaged, the fluorine-containing components will enter the environment, especially the water body, causing pollution to the environment; adding cross-linking agents will affect the storage stability and viscosity of water-based polyurethane ink. Therefore, how to improve the weather resistance of water-based polyurethane ink is still a difficult problem for researchers. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a weather-resistant water-based polyurethane ink and a preparation method thereof.

[0005] In a first aspect, the present application provides a method for preparing a weather-resistant water-based polyurethane ink, comprising the following steps: I. Prepare an aqueous polyurethane emulsion using isophorone diisocyanate and PEG-2000 in a weight ratio of 1:(1.5-3); II. Ball milling the nano-SiO2 for 0.5-1h at a temperature of 55-65°C and a rotation speed of 700-750r / min, then mixing it with polyacrylate at a weight ratio of 1:(35-40), keeping the temperature and rotation speed unchanged, ball milling for a second time for 2.5-3.5h to obtain high-dispersity nano-SiO2, then mixing it with styrene, acrylic compound and chloroether resin at a weight ratio of (1-3):13:(13-15):3.2, and reacting with the addition of an initiator, a surfactant and a silane coupling agent to obtain a modified acrylic emulsion; III. Mix and stir an aqueous polyurethane emulsion, a modified acrylic emulsion, a solvent, graphene oxide, hexagonal boron nitride, a pigment and an additive in a weight ratio of (35-40):18:20:(2.5-3):(1-1.5):5:0.4 to obtain a weather-resistant aqueous polyurethane ink.

[0006] By adopting the above technical scheme, the present invention first mixes PEG-2000 and isophorone diisocyanate, and prepares a water-based polyurethane emulsion under the condition of adding a chain extender and an initiator, making full use of the low cohesive energy and easily rotatable intermolecular ether bonds of PEG-2000, with a stable structure and not easy to hydrolyze. The obtained water-based polyurethane emulsion has the characteristics of strong water resistance, and the finally obtained weather-resistant water-based polyurethane ink also has the advantages of water resistance and flexibility. At the same time, the present invention strictly controls the weight of isophorone diisocyanate and PEG-2000. Ratio, thereby controlling the NCO / OH ratio in the system, so that the final ink has both good curing degree and flexibility. The obtained ink layer has a dense structure and is not easy to crack, and has better weather resistance. If the amount of isophorone diisocyanate used is too large, it means that the NCO / OH ratio is too large, which will reduce the flexibility of the ink layer and easily crack and break during use. If the amount of PEG-2000 used is too large, it means that the NCO / OH ratio is too small, which will reduce the curing degree of the ink, resulting in bubbles in the ink layer during curing and a decrease in surface smoothness.

[0007] Subsequently, the present application subjects the nano-SiO2 to ordinary ball milling treatment, and then adds a certain amount of polyacrylate to continue ball milling. By controlling the temperature, time and speed of ball milling, the size of the nano-SiO2 particles is effectively reduced and the specific surface area is increased. By controlling the ratio of the added amount of nano-SiO2 to the amount of polyacrylate, the shear effect during ball milling is optimized. Specifically, the polyacrylate can form a protective film to reduce the interaction force between the nano-SiO2 particles and promote dispersion. At the same time, the polyacrylate chemically grafts with the functional groups on the surface of the nano-SiO2 particles to improve the surface properties of the nano-SiO2 particles. The physical dispersion of ball milling and the synergistic chemical modification can greatly enhance the dispersibility of the nano-SiO2 particles to obtain highly dispersed nano-SiO2. Based on this, the present application blends highly dispersed nano-SiO2 with styrene, acrylic compounds and chloroether resins. The highly dispersed nano-SiO2 can be fully dispersed in the system, and styrene, acrylic compounds and chloroether resins undergo polymerization to obtain The modified acrylic emulsion is then mixed with waterborne polyurethane emulsion, solvent, graphene oxide, hexagonal boron nitride, pigment and additives in a certain weight ratio. During the mixing process, the modified acrylic emulsion and the waterborne polyurethane emulsion form hydrogen bonds through the polar hydrogen atoms on the urethane bond and the oxygen atoms on the ester group in the acrylic acid segment, thereby improving the compatibility of the two in the system. The modified acrylic emulsion has excellent water resistance, heat resistance and light aging resistance, which can greatly improve the weather resistance of waterborne polyurethane ink, and the high-dispersion nano-SiO2 can produce steric hindrance and reinforcement effects in the mixed system, thereby promoting the uniform dispersion of graphene oxide and hexagonal boron nitride. At the same time, graphene oxide and hexagonal boron nitride have a layered structure, so the good dispersion of the two themselves can in turn inhibit the agglomeration of high-dispersion nano-SiO2, and the three play a synergistic effect, which not only promotes the high dispersion of each other and inhibits agglomeration, but also can improve the strength of the ink layer and reduce the possibility of cracking in the ink layer.

[0008] In general, the present application utilizes modified acrylic emulsion and its internal highly dispersed nano-SiO2, graphene oxide and hexagonal boron nitride to coordinate and give full play to the synergistic effect, thereby greatly improving the weather resistance of the ink. After testing, the weather-resistant water-based polyurethane ink of the present application forms an ink layer after coating and curing. After artificial aging treatment (conditions are running time 480h, black standard temperature 65±2%, ambient temperature 38±3℃ and continuous running wetting and drying cycle), the gloss loss rate is not higher than 30%, the color difference value is not greater than 1.2, the powdering is very slight or even no powdering, and the peeling area is not greater than 0.1%, which has a high use value in the natural environment.

[0009] Preferably, in step I, the weight ratio of isophorone diisocyanate to PEG-2000 is 1:2.

[0010] By adopting the above technical scheme, the present application strictly controls the weight ratio of isophorone diisocyanate to PEG-2000, thereby strictly controlling the NCO / OH ratio in the system, so that the curing degree and flexibility of the final ink are optimally balanced, the obtained ink layer is not easy to crack and break, the surface flatness is high, and the weather resistance is further improved.

[0011] Preferably, in step II, the temperature for ball milling nano-SiO2 is 60°C, the time for the first ball milling is 0.8h, and the time for the second ball milling is 3h.

[0012] By adopting the above-mentioned technical scheme, the present application strictly controls the temperature and time of ball-milling nano-SiO2, greatly reduces the size difference between particles, improves dispersibility, and at the same time ensures that there is almost no structural reorganization and wear on the surface of the particles, thereby improving the uniformity of particle size distribution. Therefore, without affecting its mechanical properties, the dispersion effect of high-dispersity nano-SiO2 is improved as much as possible, thereby improving the uniformity of dispersion inside the ink layer, thereby improving its weather resistance.

[0013] Preferably, in step II, the weight ratio of high-dispersity nano-SiO2, styrene, acrylic compound and chloroether resin is 2.4:13:14:3.2.

[0014] By adopting the above technical scheme, the present application strictly controls the weight ratio of high-dispersity nano-SiO2, styrene, acrylic compounds and chloroether resin. At this time, high-dispersity nano-SiO2 can achieve better dispersion effect in the system, and the copolymer formed when styrene, acrylic compounds and chloroether resin are polymerized has higher stability. The modified acrylic emulsion finally obtained has a better polymerization effect.

[0015] Preferably, in step II, the acrylic compound comprises butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate in a weight ratio of 25:(8-13):3:(20-25):8.

[0016] By adopting the above technical scheme, the various acrylic compounds of the present application are blended with styrene and participate together in the polymerization reaction of the chloroether resin, which can balance the ratio of soft and hard segments in the system, so that the modified acrylic ester emulsion has suitable toughness and rigidity. Each acrylic compound can also give full play to its own advantages and optimize its weather resistance without affecting the mechanical properties of the water-based polyurethane emulsion.

[0017] Preferably, the weight ratio of butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate is 25:11:3:22:8.

[0018] By adopting the above technical scheme, the present application strictly controls the weight ratio of butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate. At this time, the synergistic effect between various acrylic compounds can be maximized, the number of soft and hard segments in the system is further balanced, and the synergistic effect with styrene is optimized, thereby greatly improving the weather resistance of water-based polyurethane ink.

[0019] Preferably, in step III, the weight ratio of the aqueous polyurethane emulsion to the modified acrylic ester emulsion is 38:18.

[0020] By adopting the above technical scheme, the present application strictly controls the weight ratio of the aqueous polyurethane emulsion and the modified acrylic ester emulsion. At this time, the two emulsions have good compatibility, good overall water resistance, heat resistance, and light aging resistance, and the toughness and rigidity are also in a better balance. The final aqueous polyurethane ink has better weather resistance.

[0021] Preferably, in step III, the weight ratio of the modified acrylic emulsion, graphene oxide and hexagonal boron nitride is 18:2.7:1.2.

[0022] By adopting the above technical solution, the present application strictly controls the ratio between the various substances, so that the weather resistance of the final water-based polyurethane ink is further improved.

[0023] In a second aspect, the present application provides a weather-resistant water-based polyurethane ink prepared by the preparation method of the above-mentioned weather-resistant water-based polyurethane ink.

[0024] In summary, this application has the following beneficial technical effects: 1. The present application utilizes modified acrylic emulsion to significantly improve the weather resistance of water-based polyurethane emulsion. According to testing, the ink layer formed by coating and curing the weather-resistant water-based polyurethane ink of the present application has a gloss loss rate of no more than 30% and a color difference value of no more than 1.2 after artificial aging treatment (under the conditions of 480 hours of operation time, 65±2% of black standard temperature, 38±3°C of ambient temperature, and continuous operation of wetting and drying cycles). The powdering is very slight or even non-existent, and the peeling area is no more than 0.1%, which has a high use value in the natural environment; 2. This application controls important process parameters and feed ratios, and utilizes highly dispersed nano-SiO2, graphene oxide and hexagonal boron nitride to cooperate with each other, thereby significantly optimizing the weather resistance of waterborne polyurethane emulsion without negatively affecting its mechanical properties. DETAILED DESCRIPTION

[0025] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: PEG-2000 was purchased from Haian Petrochemical Plant, Jiangsu Province; Isophorone diisocyanate was purchased from Anhui Jinyueguan New Material Technology Co., Ltd.; Dibutyltin dilaurate was purchased from Jinan Hongboli Chemical Co., Ltd.; Butyl acrylate, hydroxyethyl acrylate, isooctyl acrylate, methyl methacrylate, and methacrylic acid were purchased from Sinopharm Chemical Reagents; Polyacrylate was purchased from Shanghai Kaiyin Chemical Co., Ltd., with a total exchange capacity of ≥10.8 mmol / g (dry); The chloroether resin was purchased from BASF, model MP-45, CAS number; Sodium olefin sulfonate was purchased from Jining Fangyu Chemical Co., Ltd., CAS No. 68439-57-6; Ammonium persulfate was purchased from Maclean; Graphene oxide was purchased from Jiangxi Shuobang New Material Technology Co., Ltd., with a sieve particle size of 0.335-4 μm; Hexagonal boron nitride was purchased from Aladdin, with an average particle size of 1-2um; The wetting agent was purchased from Hangzhou Lin'an Digao Organic Chemical Co., Ltd., model TEGO-245; The leveling agent was purchased from BYK Chemicals, model number BYK-306; The drying agent was purchased from Shanghai Tianyu Chemical Technology Co., Ltd., model A-16; The defoamer was purchased from Xipusen New Materials (Ningbo) Co., Ltd., model DF800; Hydrophilic titanium dioxide was purchased from Jiangsu Hehai Nanotechnology Co., Ltd., model NY-010A.

[0026] The present application is further described in detail below with reference to examples and comparative examples.

[0027] Example 1.1 A method for preparing a weather-resistant water-based polyurethane ink comprises the following steps: I. 4.8 kg of PEG-2000 was heated and melted at 60° C. When more than 60% of the PEG-2000 was melted, stirring was started, the temperature was raised to 110° C., and the system was evacuated to a vacuum degree of 0.08 MPa. Dehydration was performed for 2 h under this environment. Subsequently, 1.6 kg of isophorone diisocyanate and 48 g of dibutyltin dilaurate were added, blended and dispersed in acetone, the system temperature was adjusted to 70° C., and the polyurethane ionomer was obtained after reaction for 1.5 h. Water was added and stirred for phase transfer, and acetone was recovered by distillation to obtain an aqueous polyurethane emulsion; II. Ball mill 4 kg of nano-SiO2 at 65 ° C and 700 r / min for 0.5 h, then mix it with 160 kg of polyacrylate, keep the temperature and speed unchanged, and ball mill for a second time for 3.5 h to obtain high-dispersity nano-SiO2; then mix 1 kg of high-dispersity nano-SiO2, 13 kg of styrene, 15 kg of acrylic compounds (10 kg of butyl acrylate, 1.25 kg of methacrylic acid and 3.75 kg of methyl methacrylate) and 3.2 kg of chloroether resin, and divide the resulting mixture into two parts by weight, one part of which is mixed with 17.6 kg of deionized water, 240 g of sodium bicarbonate and 640 g of sodium olefin sulfonate, and stirred at 650 rpm for 30 min. , add 600g of 5wt% ammonium persulfate solution, stir at 250rpm, raise the system temperature to 70℃ at a biological speed of 5℃ / min, then add 600g of 5wt% ammonium persulfate solution, raise the system temperature to 80℃, and react at constant temperature for 15min, then add another weight portion of the mixed solution and 4.2kg of 5wt% ammonium persulfate solution to the system, keep warm for 3h, then add 600g of 5wt% ammonium persulfate solution, keep warm for 1.5h, turn off the heating after the reaction but do not stop stirring, until the system temperature drops to about 40℃, add ammonia water to adjust the system pH>7, continue stirring for 20min, filter through a 200-mesh filter to obtain a modified acrylic emulsion; III. Add 3.5 kg of the aqueous polyurethane emulsion obtained in step I, 1.8 kg of the modified acrylic emulsion obtained in step II, 250 g of graphene oxide, 150 g of hexagonal boron nitride, 500 g of pigment (hydrophilic titanium dioxide) and 40 g of additives (10 g of wetting agent, 5 g of leveling agent, 10 g of defoaming agent and 20 g of drying agent) into deionized water, control the solid content in the system to 30±0.5%, and stir at a speed of 600 r / min to obtain a weather-resistant aqueous polyurethane ink.

[0028] Example 1.2 A method for preparing a weather-resistant water-based polyurethane ink comprises the following steps: I. 3.84 kg of PEG-2000 was heated and melted at 60° C. When more than 60% of the PEG-2000 was melted, stirring was started, the temperature was raised to 110° C., and the system was evacuated to a vacuum degree of 0.08 MPa. Dehydration was performed for 2 h under this environment. Subsequently, 2.56 kg of isophorone diisocyanate and 48 g of dibutyltin dilaurate were added, mixed and dispersed in acetone, the system temperature was adjusted to 70° C., and the polyurethane ionomer was obtained after the reaction for 1.5 h. Water was added and stirred for phase transfer, and the acetone was recovered by distillation to obtain an aqueous polyurethane emulsion; II. Ball mill 4 kg of nano-SiO2 at 55°C and 750 r / min for 1 h, then mix it with 140 kg of polyacrylate, keep the temperature and speed unchanged, and ball mill for a second time for 2.5 h to obtain high-dispersity nano-SiO2; then mix 3 kg of high-dispersity nano-SiO2, 13 kg of styrene, 13 kg of acrylic compound (8.7 kg of butyl acrylate, 1.08 kg of methacrylic acid and 3.22 kg of methyl methacrylate) and 3.2 kg of chloroether resin, and divide the resulting mixture into two parts by weight, one part of which is mixed with 16.5 kg of deionized water, 225 g of sodium bicarbonate and 600 g of sodium olefin sulfonate, and stirred at 650 rpm for 30 min. 560 g of 5 wt% ammonium persulfate solution was added, and the system temperature was raised to 70°C at a biological speed of 5°C / min while stirring at a speed of 250 rpm. Then 560 g of 5 wt% ammonium persulfate solution was added, and the system temperature was raised to 80°C. The mixture was reacted at a constant temperature for 15 minutes. At this time, another weight portion of the mixed solution and 4.4 kg of 5 wt% ammonium persulfate solution were added to the system, and the mixture was kept warm for 3 hours. Then 560 g of 5 wt% ammonium persulfate solution was added, and the mixture was kept warm for 1.5 hours. After the reaction was completed, the heating was turned off but the stirring was not stopped until the system temperature dropped to about 40°C. Ammonia water was added to adjust the system pH>7, and the mixture was stirred for 20 minutes. The mixture was filtered through a 200-mesh filter to obtain a modified acrylic emulsion. III. Add 4 kg of the aqueous polyurethane emulsion obtained in step I, 1.8 kg of the modified acrylic emulsion obtained in step II, 300 g of graphene oxide, 100 g of hexagonal boron nitride, 500 g of pigment (hydrophilic titanium dioxide) and 40 g of additives (10 g of wetting agent, 5 g of leveling agent, 10 g of defoaming agent and 20 g of drying agent) into deionized water, control the solid content in the system to 30±0.5%, and stir at a speed of 600 r / min to obtain a weather-resistant aqueous polyurethane ink.

[0029] Example 1.3 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step III, the amount of the water-based polyurethane emulsion obtained in step I is 3.8 kg, and the rest is the same as Example 1.1.

[0030] Example 1.4 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step III, the amount of graphene oxide used is 270 g, the amount of hexagonal boron nitride used is 120 g, and the rest is the same as Example 1.1.

[0031] Example 1.5 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step III, the amount of the water-based polyurethane emulsion obtained in step I is 3.8 kg, the amount of graphene oxide is 270 g, and the amount of hexagonal boron nitride is 120 g, and the rest is the same as Example 1.1.

[0032] Example 2.1 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step I, the amount of isophorone diisocyanate used is 2.35 kg, the amount of PEG-2000 used is 4.05 kg, and the rest is the same as Example 1.1.

[0033] Example 2.2 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step I, the amount of isophorone diisocyanate used is 2.13 kg, the amount of PEG-2000 used is 4.27 kg, and the rest is the same as Example 1.1.

[0034] Example 2.3 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step I, the amount of isophorone diisocyanate used is 1.98 kg, the amount of PEG-2000 used is 4.42 kg, and the rest is the same as Example 1.1.

[0035] Example 2.4 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step I, the amount of isophorone diisocyanate used is 1.83 kg, the amount of PEG-2000 used is 4.57 kg, and the rest is the same as Example 1.1.

[0036] Example 2.5 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step I, the amount of isophorone diisocyanate used is 1.72 kg, the amount of PEG-2000 used is 4.68 kg, and the rest is the same as Example 1.1.

[0037] Example 3.1 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step II, the temperature of ball milling nano-SiO2 is 60°C, the time of the first ball milling is 0.8h, and the time of the second ball milling is 3h, and the rest is the same as Example 1.1.

[0038] Example 3.2 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step II, the temperature of ball milling nano-SiO2 is 65°C, the time of the first ball milling is 0.8h, and the time of the second ball milling is 3h, and the rest is the same as Example 1.1.

[0039] Example 3.3 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step II, the temperature of ball milling nano-SiO2 is 60°C, the time of the first ball milling is 0.6h, and the time of the second ball milling is 3.4h, and the rest is the same as Example 1.1.

[0040] Example 4.1 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step II, the amount of high-dispersity nano-SiO2 used is 2.4 kg, the amount of acrylic compound used is 14 kg (9.35 kg butyl acrylate, 1.15 kg methacrylic acid and 3.49 kg methyl methacrylate), and the rest is the same as Example 1.1.

[0041] Example 4.2 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step II, the amount of high-dispersity nano-SiO2 used is 2 kg, the amount of acrylic compound used is 14 kg (9.35 kg butyl acrylate, 1.15 kg methacrylic acid and 3.49 kg methyl methacrylate), and the rest is the same as Example 1.1.

[0042] Example 4.3 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 1.1 in that: in step II, the amount of high-dispersion nano-SiO2 used is 2.4 kg, the amount of acrylic compound used is 14.5 kg (9.68 kg butyl acrylate, 1.19 kg methacrylic acid and 3.63 kg methyl methacrylate), and the rest is the same as Example 1.1.

[0043] Example 5.1 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 4.1 in that: in step II, the acrylic compound is 5.07 kg of butyl acrylate, 1.62 kg of hydroxyethyl acrylate, 0.62 kg of methacrylic acid, 5.07 kg of isooctyl acrylate and 1.62 kg of methyl methacrylate, and the rest is the same as Example 4.1.

[0044] Example 5.2 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 4.1 in that: in step II, the acrylic compound is 5.07 kg of butyl acrylate, 2.63 kg of hydroxyethyl acrylate, 0.62 kg of methacrylic acid, 4.06 kg of isooctyl acrylate and 1.62 kg of methyl methacrylate, and the rest is the same as Example 4.1.

[0045] Example 5.3 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 5.1 in that: in step II, the amount of hydroxyethyl acrylate used is 1.9 kg, the amount of isooctyl acrylate used is 4.79 kg, and the rest is the same as Example 5.1.

[0046] Example 5.4 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 5.1 in that: in step II, the amount of hydroxyethyl acrylate used is 2.23 kg, the amount of isooctyl acrylate used is 4.46 kg, and the rest is the same as Example 5.1.

[0047] Example 5.5 A method for preparing a weather-resistant water-based polyurethane ink, which is different from Example 5.1 in that: in step II, the amount of hydroxyethyl acrylate used is 2.45 kg, the amount of isooctyl acrylate used is 4.24 kg, and the rest is the same as Example 5.1.

[0048] Comparative Example 1.1 The difference from Example 1.1 is that in step I, the amount of isophorone diisocyanate used is 3.2 kg, the amount of PEG-2000 used is 3.2 kg, and the rest is the same as Example 1.1.

[0049] Comparative Example 1.2 The difference from Example 1.1 is that in step I, the amount of isophorone diisocyanate used is 1 kg, the amount of PEG-2000 used is 5.4 kg, and the rest is the same as Example 1.1.

[0050] Comparative Example 2.1 The difference from Example 1.1 is that the highly dispersed nano-SiO2 in step II is removed, and the rest is the same as Example 1.1.

[0051] Comparative Example 2.2 The difference from Example 1.1 is that in step II, the amount of high-dispersion nano-SiO2 used is 0.8 kg, and the rest is the same as Example 1.1.

[0052] Comparative Example 2.3 The difference from Example 1.1 is that in step II, the amount of high-dispersion nano-SiO2 used is 3.5 kg, and the rest is the same as Example 1.1.

[0053] Comparative Example 3.1 The difference from Example 1.1 is that in step II, the amount of acrylic compound used is 10 kg (6.7 kg butyl acrylate, 0.83 kg methacrylic acid and 2.47 kg methyl methacrylate), and the rest is the same as Example 1.1.

[0054] Comparative Example 3.2 The difference from Example 1.1 is that in step II, the amount of acrylic compound used is 18 kg (12 kg butyl acrylate, 1.5 kg methacrylic acid and 4.5 kg methyl methacrylate), and the rest is the same as Example 1.1.

[0055] Comparative Example 4.1 The difference from Example 1.1 is that in step III, the amount of the aqueous polyurethane emulsion prepared in step I is 3 kg, the amount of the modified acrylic emulsion prepared in step II is 2.3 kg, and the rest is the same as Example 1.1.

[0056] Comparative Example 4.2 The difference from Example 1.1 is that in step III, the amount of the aqueous polyurethane emulsion prepared in step I is 4 kg, the amount of the modified acrylic emulsion prepared in step II is 1.3 kg, and the rest is the same as Example 1.1.

[0057] Comparative Example 5.1 The difference from Example 1.1 is that in step III, the amount of graphene oxide used is 200 g, the amount of hexagonal boron nitride used is 200 g, and the rest is the same as Example 1.1.

[0058] Comparative Example 5.2 The difference from Example 1.1 is that in step III, the amount of graphene oxide used is 350 g, the amount of hexagonal boron nitride used is 50 g, and the rest is the same as Example 1.1.

[0059] Performance Testing The water-based polyurethane ink obtained in the embodiment and the comparative example was applied to the tinplate, and the wet film thickness was controlled to be 8-10um. Then, the ink layer sample was cured for 10-15h at a temperature of 23±℃ and a relative humidity of 50±5%. Four completely identical samples were prepared for each group of embodiments or comparative examples, one of which was placed in a dark place as a control plate, and the other three samples were artificially aged according to the method in GB / T 1865-2009. The ink layer sample was placed on a sample rack made of inert material to ensure the surrounding air circulation. The sample was irradiated with a xenon lamp, and the average irradiance on the surface of the ink layer sample between 300-400nm was controlled to be 60W / m 2 , black standard temperature 65±2%, ambient temperature 38±3℃, and continuous wetting and drying cycle of 18min wetting and 102min drying. The relative humidity during drying should be between 40-60%, and the radiation exposure should not be interrupted during the wetting process. The controlled running time is 480h. After the end, the average values ​​of the four data of gloss loss rate, color difference value, powdering condition and peeling area of ​​the three identical samples in each group are measured, and the results are recorded in Table 1; in: The gloss loss rate (%) is measured in accordance with GB / T 9754-2007; The color difference value is measured in accordance with GB / T 11186.2 and GB / T 11186.3; The degree of powdering is measured according to ISO 4628-7, and the grade evaluation is recorded. Grade 0 is no powdering, grade 1 is very slight powdering (pigment particles can just be observed on the test cloth), grade 2 is slight powdering (a small amount of pigment particles are stained on the test cloth), grade 3 is obvious powdering (a large number of pigment particles are stained on the test cloth), grade 4 is heavy powdering (a lot of pigment particles are stained on the test cloth), and grade 5 is severe powdering (the test cloth is full of pigment particles or the sample is exposed); The peeling area (%) was measured in accordance with GB / T 1766-2008.

[0060] Table 1 Performance test table

[0061] Data Analysis: As can be seen from Table 1, the gloss loss rate of Examples 1.1-1.2 is 29.8-30.0%, the color difference value is 1.2, the powdering level is 1, and the peeling area is 0.098-0.099%, which proves that the present application uses the modified acrylic emulsion and the high-dispersion nano-SiO2, graphene oxide and hexagonal boron nitride in it to make full use of the synergistic effect, thereby greatly improving the weather resistance of the ink; The difference between Example 1.1 and Example 1.5 is that the weight ratios of the aqueous polyurethane emulsion, the modified acrylic emulsion, the graphene oxide and the hexagonal boron nitride in step III are different. The data show that the gloss loss rate, the color difference value and the peeling area of ​​Example 1.5 are all smaller than those of Example 1.1, and the powdering grade is also degraded, proving that the weather resistance of the final aqueous polyurethane ink is further improved by strictly controlling the ratio between the substances in this application, and the data of Examples 1.3-1.4 are all inferior to those of Example 1.5, proving that the aqueous polyurethane emulsion, the modified acrylic emulsion, the graphene oxide and the hexagonal boron nitride have a better synergistic effect under the optimized weight ratio; The difference between Examples 2.1-2.5 and Example 1.1 is that in step I, the weight ratio of isophorone diisocyanate and PEG-2000 is different, and the data of Example 2.2 is significantly better than those of other groups, proving that the present application strictly controls the weight ratio of isophorone diisocyanate to PEG-2000, thereby strictly controlling the NCO / OH ratio in the system, so that the curing degree and flexibility of the final ink are optimally balanced, and the obtained ink layer is not easy to crack and break, has a high surface flatness, and further improves weather resistance; The difference between Examples 3.1-3.3 and Example 1.1 is that in step II, the temperature and time of ball milling nano-SiO2 are different, and the data of Example 3.1 is significantly better than those of other groups, proving that the present application greatly reduces the difference in particle size by strictly controlling the temperature and time of ball milling nano-SiO2, improves dispersibility, and ensures that there is almost no structural reorganization and wear on the particle surface, thereby improving the uniformity of particle size distribution, thereby improving the dispersion effect of high-dispersity nano-SiO2 as much as possible without affecting its mechanical properties, thereby improving the uniformity of dispersion inside the ink layer, thereby improving its weather resistance; The difference between Examples 4.1-4.3 and Example 1.1 is that in step II, the weight ratio of high-dispersity nano-SiO2 and acrylic compounds is different, and the data of Example 4.1 is significantly better than those of other groups, which proves that the present application achieves a better dispersion effect of high-dispersity nano-SiO2 in the system by strictly controlling the weight ratio of the two, and the copolymer formed when styrene, acrylic compounds and chloroether resin are polymerized has higher stability, and the modified acrylic emulsion finally obtained has a better polymerization effect; The difference between Examples 5.1-5.2 and Example 4.1 is that in step II, the composition of the acrylic compound is different, and the data of Examples 5.1-5.2 are significantly better than those of Example 4.1, which proves that the present application can balance the ratio of soft and hard segments in the system by blending multiple compounds of butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate with styrene and participating in the polymerization reaction of the chloroether resin together, so that the modified acrylic ester emulsion has suitable toughness and rigidity, and each acrylic compound can also give full play to its own advantages, and optimize its weather resistance without affecting the mechanical properties of the waterborne polyurethane emulsion; The difference between Examples 5.3-5.5 and Example 5.1 is that in step II, the weight ratios of butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate are different, and the data of Example 5.4 is significantly better than those of other groups, proving that the present application strictly controls the weight ratios of butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate, so that the synergistic effect between the various acrylic compounds can be maximized, the number of soft and hard segments in the system is further balanced, and the synergistic effect with styrene is optimized, thereby greatly improving the weather resistance of the water-based polyurethane ink; The data of Comparative Examples 1.1-1.2 are all inferior to those of Example 1.1, which proves that the present invention strictly controls the weight ratio of isophorone diisocyanate to PEG-2000, thereby strictly controlling the NCO / OH ratio in the system, so that the curing degree and flexibility of the final ink are optimally balanced, and the obtained ink layer is not easy to crack and break, has a high surface flatness, and further improves weather resistance; The data of comparative example 2.1 are inferior to those of example 1.1, which proves that the present application effectively reduces the size of nano-SiO2 particles and increases the specific surface area by subjecting nano-SiO2 to ordinary ball milling and then adding a certain amount of polyacrylate to continue ball milling, and controls the temperature, time and speed of ball milling, and optimizes the shear effect during ball milling by controlling the ratio of the amount of nano-SiO2 added to the amount of polyacrylate added. Specifically, polyacrylate can form a protective film to reduce the interaction force between nano-SiO2 particles and promote dispersion, and at the same time chemically grafts with the functional groups on the surface of nano-SiO2 particles to improve the surface properties of nano-SiO2 particles. Physical dispersion by ball milling and synergistic chemical modification can greatly enhance the dispersion ability of nano-SiO2 particles. The data of Comparative Examples 2.2-2.3 are inferior to those of Example 1.1, which proves that the present application achieves a better dispersion effect of high-dispersion nano-SiO2 in the system by strictly controlling the amount of high-dispersion nano-SiO2. The data of Comparative Examples 3.1-3.2 are inferior to those of Example 1.1, which proves that the copolymer formed by the polymerization of styrene, acrylic compound and chloroether resin is more stable by strictly controlling the amount of acrylic compound used in the present application, and the modified acrylic emulsion finally obtained has a better polymerization effect; The data of Examples 4.1-4.2 are all inferior to those of Example 1.1, which proves that the weather resistance of the final aqueous polyurethane ink is further improved by strictly controlling the weight ratio of the aqueous polyurethane emulsion and the modified acrylic ester emulsion in this application; The data of Examples 5.1-5.2 are all inferior to those of Example 1.1, which proves that the weather resistance of the final water-based polyurethane ink is further improved by strictly controlling the weight ratio of graphene oxide and hexagonal boron nitride and the proportion between the various substances.

[0062] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a weather-resistant water-based polyurethane ink, characterized in that: The following steps are involved: A waterborne polyurethane emulsion is prepared by using isophorone diisocyanate and PEG-2000 in a weight ratio of 1:(1.5-3); The nano-SiO2 is ball-milled for 0.5-1h at a temperature of 55-65°C and a rotation speed of 700-750r / min, and then mixed with polyacrylate at a weight ratio of 1:(35-40), and the temperature and rotation speed are kept constant, and ball-milled for a second time for 2.5-3.5h to obtain high-dispersity nano-SiO2, and then mixed with styrene, acrylic compound and chloroether resin at a weight ratio of (1-3):13:(13-15):3.2, and reacted with the addition of an initiator, a surfactant and a silane coupling agent to obtain a modified acrylic emulsion; Aqueous polyurethane emulsion, modified acrylic emulsion, graphene oxide, hexagonal boron nitride, pigment and additives in a weight ratio of (35-40):18:(2.5-3):(1-1.5):5:0.4 are dispersed in a solvent and uniformly mixed to obtain a weather-resistant aqueous polyurethane ink.

2. The method for preparing a weather-resistant water-based polyurethane ink according to claim 1, characterized in that: In the step I, the weight ratio of isophorone diisocyanate to PEG-2000 is 1:

2.

3. The method for preparing a weather-resistant water-based polyurethane ink according to claim 1, characterized in that: In the step II, the temperature for ball milling nano-SiO2 is 60°C, the time for the first ball milling is 0.8h, and the time for the second ball milling is 3h.

4. The method for preparing a weather-resistant water-based polyurethane ink according to claim 1, characterized in that: In the step II, the weight ratio of high-dispersity nano-SiO2, styrene, acrylic compound and chloroether resin is 2.4:13:14:3.

2.

5. The method for preparing a weather-resistant water-based polyurethane ink according to claim 1, characterized in that: In the step II, the acrylic compound includes butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate in a weight ratio of 25:(8-13):3:(20-25):

8.

6. The method for preparing a weather-resistant water-based polyurethane ink according to claim 5, characterized in that: The weight ratio of butyl acrylate, hydroxyethyl acrylate, methacrylic acid, isooctyl acrylate and methyl methacrylate is 25:11:3:22:

8.

7. The method for preparing a weather-resistant water-based polyurethane ink according to claim 1, characterized in that: In the step III, the weight ratio of the aqueous polyurethane emulsion to the modified acrylic ester emulsion is 38:

18.

8. The method for preparing a weather-resistant water-based polyurethane ink according to claim 1, characterized in that: In the step III, the weight ratio of the modified acrylic emulsion, graphene oxide and hexagonal boron nitride is 18:2.7:1.

2.

9. A weather-resistant water-based polyurethane ink prepared by the method for preparing the weather-resistant water-based polyurethane ink according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Flexography waterborne ultraviolet (UV) printing ink and preparation method thereof

    CN103275551A

  • Water-based UV printing ink and preparation method thereof

    CN107629541A

  • Sun-proof and waterproof ink and preparation method thereof

    CN111621196A

  • Waterborne polyurethane printing ink and preparation process thereof

    CN118879121A

  • Aqueous polyurethane resin and use of the same

    JP2013234214A